Agile Development of PHP Websites: A Model-Aware Approach - Carmen Ioana Gog (Complex Systems Informatics and Modeling Quarterly)
The Design Science research method was hereby employed to develop an artifact that demonstrates the experimental “model-aware” software engineering methodology in the context of PHP Web development – a “low code” development approach with code templates generated from technology-specific models. The proof-of-concept consists of two interacting components: a custom diagrammatic modeling environment and model-driven generated PHP pages. The interaction between the two components conforms the engineering method labelled as “Model-aware software engineering” (MASE) – a flavor of model-driven engineering recently introduced in research projects as a hybridization of the Agile Modeling Method Engineering (AMME) framework and the Resource Description Framework (RDF). The experimental MASE method is employed here to demonstrate its feasibility for the common Model-View-Controller (MVC) website development pattern, thus showing potential to support common Web development work.